Design optimisation of C ion implantation of α-Al2O3 for medical dosimetry. (5th September 2018) - Agarwal, Mini; Garg, S.K.; Asokan, K.; Thulkar, S.; Chander, S.; Dalai, M.K.; Kumar, Pratik
Abstract: The present work reports the fabrication and characterization of α–Al2 O3 :C, a highly sensitive low effective atomic number (Zeff  = 10.7) OSL material for medical dosimetry, through a new approach of doping via implantation. In this study, a Single Crystalline α–Al2 O3 (SCALO) and a Sapphire α–Al2 O3 (SALO) are used and implanted with 100 keV of C + at various fluences (mol%) from 2.5 × 10 14  ions cm −2 (~0.04%) to 6.25 × 10 15  ions cm −2 (~1%) and are pre-heated up to 220 °C. The structural, optical, morphological and luminescent studies of the Carbon doped α–Al2 O3 (α–Al2 O3 :C) are carried out using X-ray diffraction, Ultraviolet-visible spectroscopy (UV–Vis), Photo-luminescence (PL), Time of Flight Secondary Ion Mass Spectrometry (TOF-SIMS), Optically Stimulated Luminescence (OSL), and Thermo-Luminescence (TL). The doping of ~1 mol% of C + is found at an optimized doping level due to its high intensity of luminescence. This phenomenon is studied for heavy charged particle (HCP) dosimetry, which might prove effective for cancer treatment. It is found that α –ALO:C (both the single crystalline and the sapphire alumina) has the capability to measure large radiation doses (~kGy). This is attributed to the generation of stable defects after the incorporation of Carbon that results in a linear response with the dose and in extraordinary efficiency. Thus, this study confirms the development of α–Al2 O3 by the novel approach of C + implantation method and the findings result in an efficient medical radiation dosimeter. Graphical abstract: Present work investigates the medical dosimetric properties of 100 keV C ion implanted single crystalline α-Al2 O3 and sapphire. This is a novel method for doping for dosimetry applications. Unlabelled Image Highlights: Optimal medical dosimetric properties are found in ~1 mol% 100 keV C ion implanted single crystalline α-Al2 O3 and sapphire. C-implanted single crystal and sapphire alumina show linear response up to large radiation doses (~kGy). Presence of stable defects (C atoms) confirmed by optical band calculation, PL and OSL show linear response and re-usability.